BUDAYA KERJA GURU PENDIDIKAN DASAR UNGGUL (Studi Situs SMP Negeri 1 Gunung Jati Cirebon) - Handayani, Sri (Universitas Muhammadiyah Surakarta, 2013)
This study is aimed at describing the working culture of administration, teaching learning activities, and evaluating the teaching learning process of accelerated class of SMP 1 Gunung Jati Cirebon teachers in doing their job. This study applies the qualitative of ethnographic that is to see directly the working culture of the subject of the study such as their behavior, their motivation, their perception and their action related to good teachers working culture. The data are taken from interviews with teachers, documents related of teachers job, and field study. In collecting the data, the researcher carried our interview with teachers, doing some observations, and study the documents related to teachers? job. The data are analyzed and tested using credibility, dependability, and confirm ability tests.The results of the study are: (1) the teachers working culture in doing their administrative means how a teacher increases work such as developing syllabus, making lesson plan, developing indicators, and developing teachers materials. Teachers? working culture in developing their administration work are developed in school and region teacher forum; (2) teachers working culture in teaching learning activities means how teacher increases work such as make, introduction activity, core activity, and final activity in the teaching and learning process as indicated by the curriculum. (3) teachers working culture in evaluating the teaching learning process means how teacher increases work such as compilation planning of assessment and execution of assessment. The study suggests: (1) the headmaster should give opportunities for teacher to develop their work so that they can contribute to the administration, classroom teaching learning process, evaluation and analysis; (2) the teachers can improve their work such as the administration, classroom teaching learning process, and evaluation of study with activities or constructions by school, duty education, and related institute; (3) the researcher, moreover, should conduct the study concerning the teacher working culture better.